Pengaruh Kualitas Komunikasi Organisasi Terhadap Kesiapan Individu Untuk Perubahan: Peran Komitmen Terhadap Perubahan Sebagai Variabel Moderasi - Dekal, Fine Sepra; Suardesi, Suardesi; Zaitul, Zaitul (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze the influence of organizational communication quality on individual readiness for change by considering the role of commitment to change as a moderating variable. Based on organizational communication theory and organizational change theory, the hypothesis is proposed that good quality organizational communication will increase individual readiness for change, and commitment to change will moderate this relationship. The research method used is a quantitative approach, which collects primary. Primary data was obtained through a survey. The results of the analysis show that the quality of organizational communication has a significant positive influence on individual readiness for change. In addition, it was found that commitment to change moderates this relationship, where the influence of organizational communication quality on individual readiness for change becomes stronger under conditions of high commitment to change. These findings show the importance of paying attention to the quality of organizational communication and building commitment to change in managing change in the work environment. The practical implication of this research is that organizations need to improve effective internal communication and strengthen commitment to change among employees.